Novel Psychoactive Substances in Young Adults with and without Psychiatric Comorbidities - Martinotti, Giovanni (Hindawi Publishing Corporation, 2014)
Objective. Comorbidities between psychiatric diseases and consumption of traditional substances of abuse (alcohol, cannabis, opioids, and cocaine) are common. Nevertheless, there is no data regarding the use of novel psychoactive substances (NPS) in the psychiatric population. The purpose of this multicentre survey is to investigate the consumption of a wide variety of psychoactive substances in a young psychiatric sample and in a paired sample of healthy subjects. Methods. A questionnaire has been administered, in different Italian cities, to 206 psychiatric patients aged 18 to 26 years and to a sample of 2615 healthy subjects matched for sex, gender, and living status. Results. Alcohol consumption was more frequent in the healthy young population compared to age-matched subjects suffering from mental illness (79.5% versus 70.7%; P < 0.003). Conversely, cocaine and NPS use was significantly more common in the psychiatric population (cocaine 8.7% versus 4.6%; P = 0.002) (NPS 9.8% versus 3%; P < 0.001). Conclusions. The use of novel psychoactive substances in a young psychiatric population appears to be a frequent phenomenon, probably still underestimated. Therefore, careful and constant monitoring and accurate evaluations of possible clinical effects related to their use are necessary.